2017
DOI: 10.1021/acs.energyfuels.7b02437
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Novel Surfactant To Prepare Oil-in-Water Emulsion of an Indian Heavy Crude Oil for Pipeline Transportation

Abstract: This article thoroughly evaluates the performance of a synthesized surfactant as an emulsifier for the preparation of an Indian heavy crude oil-in-water (o/w) emulsion to enhance its ability to flow through offshore pipelines. The physicochemical characteristics, wax content, wax appearance temperature, FT-IR spectrum, and high-temperature gas chromatogram of the heavy crude oil were analyzed first. High-frequency (26 kHz) ultrasonic waves were utilized to disperse heavy crude oil in water. Further evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 44 publications
1
35
0
Order By: Relevance
“…Thus, reduction in droplet size results in more stable as well as a viscous emulsion, due to increased number of droplets, large interfacial area, and hence increased particle to particle interactions. Similar results have been observed by various researchers (Abdurahman et al, 2012; Ahmed et al, 1999; Ashrafizadeh and Kamran, 2010; Kumar and Mahto, 2017). From Fig.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Thus, reduction in droplet size results in more stable as well as a viscous emulsion, due to increased number of droplets, large interfacial area, and hence increased particle to particle interactions. Similar results have been observed by various researchers (Abdurahman et al, 2012; Ahmed et al, 1999; Ashrafizadeh and Kamran, 2010; Kumar and Mahto, 2017). From Fig.…”
Section: Resultssupporting
confidence: 91%
“…Further, the presence of polyaromatic structure is also observed with weak bending vibrations at 746.04, 813.75, and 869.49 cm −1 . The presence of such aromatic and polyaromatic structures in HCO represents the presence of asphaltenes and resins in HCO (Kumar et al, 2018; Kumar and Mahto, 2017). Weak peaks at 722.16 and 587.97 cm −1 represent rocking vibrations of carbon chain having six or more carbon atoms/more than four methyl groups in HCO.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nanoemulsions have the potential to reduce IFT and, accordingly, the capillary pressure of the reservoir [ 1 ], improve rock wettability [ 1 ], ease the fracturing fluid flow-back [ 21 ], eliminate phase trapping [ 21 , 22 ], and increase the regained gas permeability [ 1 , 21 ]. Accordingly, some researchers have recently demonstrated the applicability of nanoemulsions in enhanced oil recovery (EOR) [ 23 , 24 , 25 ], production enhancement (e.g., well stimulation and remediation, well-bore cleaning, and formation fracturing) [ 26 , 27 , 28 ], and pumping of extra heavy crude oil [ 29 ]. For instance, it has been reported that nanoemulsions can (i) minimize/control water-cut [ 28 ], (ii) create new channels for gas flow (i.e., increase gas permeability) [ 28 ], (iii) increase proppant permeability and, accordingly, lower the initial cleanup pressure [ 30 ], (iv) reduce fingering [ 31 ], (v) enhance the flow-back rates of fracturing fluids [ 31 ], (vi) reduce/eliminate water blocking problems [ 27 ], and (vii) minimize surfactant adsorption to the reservoir rocks [ 1 ], among other beneficial effects.…”
Section: Introductionmentioning
confidence: 99%